Integration of Oil Palm and Cattle to Empower Farmers’ Economic in East Aceh, Indonesia - Saifuddin Yunus; Suadi Zainal; Suryadi .; Fadli Jalil (Proceedings of AICS - Social Sciences, 2016)
This study examines the integration of oil palm commodities and cattle to empower farmers’ economic in East Aceh, Aceh Province, Indonesia. Even though, this paper only focus on empowerment process with aim to discover an integration process of oil palm and cattle made by oil palm farmers. This study used a qualitative approach to analyze data. The results showed that the process of integration of oil palm and cattle are practiced by oil palm farmers without adequate knowledge. In addition, the integration also has done between cattle breeders and oil palm farmers. However local authorities (Aceh Province and East Aceh) have not given the attention for this program to empower the farmers with education and training skill to integrate oil palm and cattle. Whereas such as this program is commonly practiced in Indonesia.